Coronary artery disease, left ventricular hypertrophy and diastolic dysfunction are associated with stroke in patients affected by persistent non-valvular atrial fibrillation: a case-control study - Andrea Passantino; Pasquale Palmiero; Maria Maiello (Heart International, 2009)
Persistent non-valvular atrial fibrillation (NVAF) is associated with an increased risk of cardiovascular events such as stroke, and its rate is expected to rise because of the ageing population. The absolute rate of stroke depends on age and comorbidity. Risk stratification for stroke in patients with NVAF derives from populations enrolled in randomized clinical trials. However, participants in clinical trials are often not representative of the general population. Many stroke risk stratification scores have been used, but they do not include transthoracic echocardiogram (TTE), pulsate wave Doppler (PWD) and tissue Doppler imaging (TDI), simple and non-invasive diagnostic tools. The role of TTE, PWD and TDI findings has not been previously determined. Our study goal was to determine the association between TTE and PWD findings and stroke prevalence in a population of NVAF prone outpatients. Patients were divided into two groups: P for stroke prone and F for stroke free. There were no statistically significant differences between the two groups concerning cardiovascular risk factors, age (p=0.2), sex (p=0.2), smoking (p=0.3), diabetes (p=0.1) and hypercholesterolemia (p=0.2); hypertension was statistically significant (p less than 0.001). There were statistically significant differences concerning coronary artery disease, previous acute myocardial infarction (AMI) (p less than 0.05) and non- AMI coronaropathy (p less than 0.04), a higher rate being in the P group. Concerning echo-Doppler findings, a higher statistically significant rate of left ventricular hypertrophy (LVH) (p less than 0.05) and left ventricular diastolic dysfunction (p less than 0.001) was found in the P group and dilated left atrium (p less than 0.04) in the F group, the difference was not significant for mitral regurgitation (p=0.7). Stroke prone NVAF patients have a higher rate of hypertension, coronary artery disease, with and without AMI, LVH and left ventricular diastolic dysfunction, but not left atrial dilatation. M-B mode echocardiography and PWD examination help to identify high-risk stroke patients among NVAF subjects; therefore, they may help in the selection of appropriate therapy for each patient.